Multiple Approaches for Individualized Fertility Protective Therapy in Cancer Patients. (29th December 2011) - Demeestere, I.; Moffa, F.; Peccatori, F.; Poirot, C.; Shalom-Paz, E.
Abstract : In the last decade, fertility preservation has risen as a major field of interest, creating new interactions between oncologists and gynecologists. Various options, such as cryopreservation of ovarian tissue, have been developed and are currently routinely proposed in many centers. However, many of the options remain experimental and should be offered to patients only after adequate counseling. This paper addresses the efficiency and the potential of the different fertility preservation approaches.